Contribution of remuneration and staff motivation to improving the performance of Algerian SME subcontractors - Asma Azzouz; Boudjemaa Amroune; Jamal Ben Mansour (Journal of North African Economies, 2025)
The ability of organizations to attract and retain competent personnel is linked to the incentive elements implemented. This quest for skills allows enterprises to have an important competitive position. In fact, remuneration and motivation are essential elements in attracting qualified and competent workers. However, the essential aim of this article is to prove the degree of influence of these HRM practices on the ability of enterprises to acquire the right personnel for their needs., and to participate in performance on all scales. A qualitative empirical study was carried out with several Algerian SME subcontractors in order to examine the acceptability of the proposals presented, and to support the theoretical research previously carried out. The results prove that remuneration and motivation contribute greatly to the multiple performances of Algerian SME subcontractors.